People and Families Affected by Glycogen Storage Disease Type Ia: An Analysis of Narrative Accounts Written by Individuals Living with GSDIa and Their Caregivers - Eliza Kruger; Hayley M. de Freitas; Iris Ferrecchia; Millie Gaydon; Andrew Lloyd (Journal of Health Economics and Outcomes Research)
# Background Glycogen storage disease type Ia (GSDIa) is a rare inherited disorder that can lead to renal and hepatic complications, brain damage, and death. There is a lack of qualitative research describing the impact of GSDIa on individuals and their caregivers.